ChatGPT Training for YPMAK Students at Universitas Katolik De La Salle Manado - Rafael Sengkey; Lianly Rompis; Stella Paendong; Filly Mamuaja (Journal of Innovation and Community Engagement, 2025)
ChatGPT is a virtual and important tool that can assist both lecturers and students in getting information about things they want to know, seeking clarification, and obtaining ideas related to assignments and projects. The main thing is that access to information becomes faster and more effective. In order to help the Amungme and Kamoro Community Empowerment Foundation in Mimika Regency (called Yayasan Pemberdayaan Masyarakat Amungme dan Kamaro or YPMAK in Indonesian), the Faculty Team at Universitas Katolik De La Salle Manado, consisting of lecturers from the Management, Physiotherapy, Agribusiness, and Electrical Engineering study programs, conducted a ChatGPT training for YPMAK students across these four study programs. This community service was organized by the team, with the help of the university students and alumni from October until November 2024, about technology and the English language. The team introduced the YPMAK students to ChatGPT technology and trained them on how to use it for the learning process. After the training, the team conducted a comprehension test to observe if the students could improve their knowledge of the English language, especially reading and grammar. The team also conducted a short survey to determine the students' perceptions when they learned with ChatGPT.